Temporal Integration of Sinusoidal Increments in the Absence of Absolute Energy Cues. - Formby, C.; Heinz, M. G.; Aleksandrovsky, I. V. (Journal of Speech, Language & Hearing Research, 2002)
Classical temporal integration (TI) is often viewed as a frequency-dependent, energy-based detection process. Detection thresholds for brief sinusoidal increments in either a fixed-level or a random-level broadband pedestal are reported that refute this traditional perspective of TI. Instead, evidence is presented that indicates (a) detection of absolute energy is not necessary for the TI effect and (b) the frequency dependence of TI is consistent with variations across frequency in peripheral auditory tuning, rather than the integration process per se. When peripheral frequency selectivity is controlled, TI can be explained by a frequencyinvariant integration process over at least the frequency range from 500 to 4000 Hz. This process is characterized by threshold improvements of 8-9 dB per decade increase in duration for increment durations between 10 and 300 ms. Reprinted by permission of the publisher.